A dimensão ambiental no pensamento sociológico da Universidade de Oriente, núcleo de Sucre, Campus Cumaná, Venezuela - Castel, Guillermo Ramón Velásquez (2019)
Environmental sociology is a relatively new area of study, however, with significant advances in the production of theories and methodologies that allow approaching the relationship between society and nature. On the other hand, some theorists of this field of study point out that there is still a certain inability of contemporary sociologists to approach environmental issues due to the anthropocentric heritage left by sociology classics. In this regard, this study aimed to analyze the conception of the environmental dimension in the sociological thinking of the University of Oriente, in order to determine the degree of importance that is granted to it within the Degree Program in Sociology and the Master Program in Development Planning of this university. The theoretical methodological path was divided into two phases, one exploratory based on the documentary research and another analytical-descriptive, based on the interviews. Environmental categories, defined from the currents of constructionism, critical realism, risk-formulation theory, actor-network theory and decolonial, have been identified in the different research papers developed in the last five years in these programs, including Course Conclusion, Dissertations and Ascension Works. Although, the environmental dimension was researched in the curriculum of the respective training programs and menus of the disciplines that compose it and, finally, the data obtained were contrasted with the statements of the professors interviewed of both programs. The results indicated that there is an evaluation of the importance of the study of the relation society - environment in the sociology, as well as the consideration of the sustainable development in different researches of regional development planning. However, there were some weaknesses related to the scarce proportion of researches in the area of environmental sociology, outdated theoretical contents, absence of the main currents that are currently studying environmental issues, and lack of depth in the use and analysis of the proposed environmental categories. These questions are considered as representing an incomplete conception of the environmental dimension in the sociological thought of the University of Oriente.